Does Sasaknese have Inflectional Phrase? - Hijriati, Sartika; Arief, Yusuf Al; Susanti, Ika; Rahmawati, Dian Karina (Universitas Muhammadiyah Mataram, 2025)
In generative grammar, particularly within X-bar theory, all syntactic structures are endocentric. This principle dictates that a clause or sentence must be analyzed as an inflectional phrase (IP), with the inflectional category as its head. While this principle has been attested across numerous languages and is considered universal, languages like Javanese exhibit patterns distinct from inflectional systems such as English. This study examines the existence of inflectional phrases in Sasaknese, which have not been discussed yet in any other studies of Sasak language, using data from Sasaknese book collected through observational methods. The analysis confirms that Sasaknese lexicons expressing tense, aspect, and modality belong to inflections and project maximally as an Inflectional Phrase.